Lithium extraction from geothermal brine using γ-MnO2: A case study for Tuzla geothermal power plant - Seyra Toprak; Çınar Öncel; Sinan Yılmaz; Alper Baba; Gonca Aksoy Koç; Mustafa M. Demir (Heliyon)
Geothermal brines contain high concentrations of ions and form a source of various valuable elements. The isolation of the elements from their water systems is a great challenge when the gradual depletion of ores in mining is considered. Attempts have been made for a long time to isolate valuable elements from aqueous mixtures prepared in the laboratory. However, those studies might not reflect the complexity of natural systems and might yield results that deviate significantly from the performance in real field systems. In this study, sorption is used to extract lithium ions from a representative field, Tuzla Geothermal Power Plant (TGPP) Turkey, using a mini-pilot reactor introduced to the reinjection well of the plant. Electrolytic manganese dioxide (γ-MnO2), a relatively inexpensive material widely used as the cathode material in lithium-ion batteries, was employed as a sorbent material for lithium. The sorption/desorption performance of the novel γ-MnO2 was investigated under various conditions. Sorption is performed at 360K and 2 bars. The maximum sorption performance was obtained at 1 h in Tuzla GPP. The desorption experiments were performed in acidic solutions. The concentration of Li+ in the desorption solution was found to be 25 mg/L on average when 10 g of γ-MnO2 was dispersed into 30 mL of the acidic aqueous solution. The first desorption solution was used consecutively for collecting more Li+ ions through the desorption of fresh brine-treated powder samples (cumulative desorption). By repeating this process four times consecutively, 230 mg/L of Li+ was obtained in the desorption solution. Moreover, the reusability of the γ-MnO2 sorbent was examined. The sorbent powder showed almost 40% performance efficiency compared to virgin powder under the conditions employed in this study. The use of electrolytic γ-MnO2 sorbent for lithium adsorption was found to be a promising process for practical use in the separation of lithium from geothermal brines.